RESPIRATORY MUSCLE STRENGTH BEHAVIOR IN ACTIVE AND SEDENTARY ELDERLY (Fiep Bulletin - online, 2012)
Aging brings changes in cardiorespiratory system, like the reduction in respiratory muscle strength (RMS). The aim of this study was to evaluate the respiratory muscle strength in healthy elderly active and sedentary people. It was evaluated 66 old females, 36 of those make exercises regularly (at least 3 times a week) and 30 are sedentary, all of them between 60-81 years. It was used a spirometry test to demonstrate the well function of the lung. The RMS was evaluated by the maximal lung pressures with a digital manovacuometry. The student t test to comparison between groups and Pearson correlation test were used (p
Keywords: Respiratory Muscle; Ageing; Physical Activity; Sedentary